The Leeds Assessment of Neuropathic Symptoms and Signs Scale (LANSS) is not an adequate outcome measure of pressure ulcer‐related neuropathic pain. (12th May 2016) - Rutherford, C.; Nixon, J.E.; Brown, J.M.; Briggs, M.; Horton, M.
Abstract: Background: Few pain assessment scales have been used in pressure ulcer (PU) research and none developed or validated for people with PUs. We examined the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scale to determine its utility as an outcome measure for people with pressure area‐related pain. Methods: Leeds Assessment of Neuropathic Symptoms and Signs data from 728 participants underwent psychometric analyses: traditional tests for data quality, scaling assumptions, reliability and validity and a Rasch analysis including tests of fit, spread and targeting of item locations, response dependency, person separation index (reliability) and differential item functioning. Results: Our findings offer support for a unidimensional scale; confirmatory factor analysis indicated a non‐significant chi‐square test of model fit [(df = 14) 23.48, p  = 0.053]. However, some misfit was identified at the overall scale and individual item levels, and internal construct validity of the LANSS as an outcome measure for neuropathic pain in people with pressure area‐related pain was not supported; low to moderate item‐total correlations [Chi Square (df = 28) 55.546, p  = 0.002] and inter‐item correlations (mean 0.117 and range from 0.063 to 0.415); and low Cronbach's alpha (0.549) and Person Separation Index (0.334). Conclusions: Requirements for reliable and valid measurement do not support the use of the LANSS as an outcome measure in people with PUs at the individual level or as a generalized measurement scale of neuropathic pain across ulcer severity groups. Expanding the number of items to aid differentiation between neuropathic pain levels and improving scale reliability is recommended. What does this study add?: The Leeds Assessment of Neuropathic Symptoms and Signs scale (LANSS) is not suitable as an outcome measure of pressure ulcer‐related neuropathic pain as it did not meet requirements for reliable and valid measurement in this population.